ANALISIS MUTU PELAYANAN TRANSPORTASI TRANSJAKARTA DI HALTE JELAMBAR - Indah Lestari, Dian; Putranto, Leksmono Suryo (JMTS: Jurnal Mitra Teknik Sipil, 2024)
Urban transportation is a key aspect of community mobility in the city of Jakarta. Transjakarta, as one of the largest public transportation systems in Jakarta, plays an important role in meeting the public transportation needs of city residents. Halta Jelambar is one of the most strategic stopping points in the Transjakarta network, connecting various routes and reaching various levels of society. This research aims to analyze the quality of Transjakarta transportation services at the Jelambar bus stop by considering a number of user experiences, prioritizing factors such as waiting time, cleanliness, comfort and safety analyzed in the context of user experience. So it is hoped that this research can provide the best quality service for the local community. Transportasi perkotaan adalah aspek kunci dalam mobilitas masyarakat di kota Jakarta. Transjakarta, sebagai salah satu sistem transportasi umum terbesar di Jakarta, berperan penting dalam memenuhi kebutuhan transportasi publik penduduk kota. Halte Jelambar adalah salah satu titik pemberhentian yang sangat strategis dalam jaringan Transjakarta, menghubungkan berbagai rute dan menjangkau berbagai lapisan masayrakat. Adapun penelitian ini bertujuan untuk menganalisis mutu pelayanan transportasi Transjakarta di halte jelambar dengan mempertimbangkan sejumla pengalaman pengguna, dengan mendepankan fakor-faktor seperti waktu tunggu, kebersihan, kenyamanan dan keamanan dianalisis dalam konteks pengalaman pengguna. Sehingga penelitian ini diharapkan dapat memeberikan mutu pelayanan yang terbaik bagi masyarakat setempat.